Teleology and Utopia in Alasdair MacIntyre’s Ethics and Politics - Bielskis, Andrius (Sociologija. Mintis ir veiksmas, 2008)
The paper explores Alasdair MacIntyre’s political philosophy vis-à-vis his critique of the Enlightenment project and of modernity. MacIntyre’s political thought in the Anglo-American academic world is often reduced to his critique of the critique of the institution of modern nation state. The paper provides a critique of such reductionionist interpretation. It argues that MacIntyre’s critique of modern liberal democracy will not be properly understood without taking into account his conceptions of teleology and utopia.